Heat transfer and phase transformations in the localization of forest fuel combustion; Interfacial Phenomena and Heat Transfer; Vol. 7, iss. 2 - Kuznetsov G. V. Geny Vladimirovich; Voytkov I. S. Ivan Sergeevich; Kropotova S. S. Svetlana Sergeevna; Atroshenko Yu. K. Yuliana Konstantinovna (2019, 2019)
Title screen